2019
DOI: 10.3349/ymj.2019.60.7.597
|View full text |Cite
|
Sign up to set email alerts
|

Health Effects of Radon Exposure

Abstract: Radon is a naturally occurring radioactive material that is formed as the decay product of uranium and thorium, and is estimated to contribute to approximately half of the average annual natural background radiation. When inhaled, it damages the lungs during radioactive decay and affects the human body. Through many epidemiological studies regarding occupational exposure among miners and residential exposure among the general population, radon has been scientifically proven to cause lung cancer, and radon expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(28 citation statements)
references
References 50 publications
0
24
0
4
Order By: Relevance
“…At present, the pathogenic factors of NSCLC are not completely clear, but there are many risk factors, including smoking and occupational diseases [22]. Cancer development is accompanied by many gene interactions, including circRNA regulation [23].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the pathogenic factors of NSCLC are not completely clear, but there are many risk factors, including smoking and occupational diseases [22]. Cancer development is accompanied by many gene interactions, including circRNA regulation [23].…”
Section: Discussionmentioning
confidence: 99%
“…The authors reported that indoor radon levels increased the risk of stroke after adjusting for potential confounding factors (OR: 1.004 (95 CI: 1.001–1.007), p = 0.010), and they observed an association between indoor radon exposure over 100 Bq/m 3 and this disease (OR: 1.242 (95 CI: 1.069–1.444), p = 0.005) [ 30 ]. A prospective trial in the USA found a significant association between radon exposure and mortality from chronic obstructive pulmonary disease (COPD) [ 34 ]. However, the relationship of this exposure to diseases other than lung cancer, especially leukemia and COPD, remains controversial [ 35 , 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The higher the radon concentration in the air we breathe and the longer the exposure time, the greater is the risk of developing lung cancer. According to several studies [7][8][9], the risk increases linearly due to long-term permanent exposure to high radon concentrations within the buildings. In general, radon is the major contributor to the ionizing radiation dose to which the human being is naturally exposed, and it is, therefore, essential to adopt all measures that can mitigate the presence of this gas indoors [2].…”
Section: Radon Public Health Riskmentioning
confidence: 99%